Sphingosine 1-phosphate receptor modulator ONO-4641 stimulates CD11b+Gr-1+ cell expansion and inhibits lymphocyte infiltration in the lungs to ameliorate murine pulmonary emphysema. Issue 6 (November 2018) - Asakura, Takanori; Ishii, Makoto; Namkoong, Ho; Suzuki, Shoji; Kagawa, Shizuko; Yagi, Kazuma; Komiya, Takaki; Hashimoto, Takafumi; Okamori, Satoshi; Kamata, Hirofumi; Tasaka, Sadatomo; Kihara, Akio; et al.
Abstract Sphingolipids play a pivotal role in the pathogenesis of chronic obstructive pulmonary disease (COPD). However, little is known about the precise roles of sphingosine-1-phosphate (S1P), a bioactive sphingolipid metabolite, and its receptor modulation in COPD. In this study, we demonstrated that the S1P receptor modulator ONO-4641 induced the expansion of lung CD11b+ Gr-1+ cells and lymphocytopenia in naive mice. ONO-4641-expanded CD11b+ Gr-1+ cells showed higher arginase-1 activity, decreased T cell proliferation, and lower IFN-γ production in CD3+ T cells, similar to the features of myeloid-derived suppressor cells. ONO-4641 treatment decreased airspace enlargement in elastase-induced and cigarette smoke-induced emphysema models and attenuated emphysema exacerbation induced by post-elastase pneumococcal infection, which was also associated with an increased number of lung CD11b+ Gr-1+ cells. Adoptive transfer of ONO-4641-expanded CD11b+ Gr-1+ cells protected against elastase-induced emphysema. Lymphocytopenia observed in these models likely contributed to beneficial ONO-4641 effects. Thus, ONO-4641 attenuated murine pulmonary emphysema by expanding lung CD11b+ Gr-1+ cell populations and inducing lymphocytopenia. The S1P receptor might be a promising target for strategies aimed at ameliorating pulmonary emphysema progression.